2020
DOI: 10.3389/fpubh.2020.00130
|View full text |Cite
|
Sign up to set email alerts
|

Strength Improvements of Different 10-Week Multicomponent Exercise Programs in Elderly Women

Abstract: The purpose of this study was to analyze and compare the effects of various muscle strength sessions performed during 10 weeks physical conditioning programs and 4 weeks of detraining on the physical conditioning, body composition and hematology of elderly women. 48 women were randomly distributed in four groups: a physical conditioning group (PCG; n = 12) with two sessions per week; a PCG with an extra-session focus on hypertrophy (PCGH; n = 12), a PCG with an extra-session in a shallow pool (PCGP; n = 12); a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…There were also significant improvements in "single left leg" and "single right leg" stands, showing improved balance in the older adults. These findings were consistent with those of many other studies [99][100][101][102][103][104], also showing that improved lower extremity strength leads to neurological integrity and reduces the risk of fall in older adults. In addition, from the perspective of older adults' adherence to exercise, after the implementation of the multi-component exercise pro-gram, it was found that the variety of exercises intrinsically motivated older adults to exercise, and the attendance rates of males and females reached 95% and 97%, respectively, demonstrating their exercise adherence [50,51].…”
Section: Discussionsupporting
confidence: 92%
“…There were also significant improvements in "single left leg" and "single right leg" stands, showing improved balance in the older adults. These findings were consistent with those of many other studies [99][100][101][102][103][104], also showing that improved lower extremity strength leads to neurological integrity and reduces the risk of fall in older adults. In addition, from the perspective of older adults' adherence to exercise, after the implementation of the multi-component exercise pro-gram, it was found that the variety of exercises intrinsically motivated older adults to exercise, and the attendance rates of males and females reached 95% and 97%, respectively, demonstrating their exercise adherence [50,51].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the gray‐scale US found no difference in the anatomic dimensions between pincer‐type FAI and volunteer groups, whereas SWE revealed that there was a significant difference in muscle elasticity between the two groups. This is similar as resistance training can increase muscle strength in patients with sarcopenia without changing their body composition and morphology 17,18 . More interesting, in the external rotation position, there were significant differences between pincer‐type FAI patients and volunteers in both maximum and mean elastic values, whereas in a neutral position, only mean values were statistically different.…”
Section: Discussionsupporting
confidence: 52%
“…This is similar as resistance training can increase muscle strength in patients with sarcopenia without changing their body composition and morphology. 17,18 More interesting, in the external rotation position, there were significant differences between pincer-type FAI patients and volunteers in both maximum and mean elastic values, whereas in a neutral position, only mean values were statistically different. This might be attributed to the fact that iliocapsularis muscle atrophy was not obvious enough to be observed in a neutral position.…”
Section: Discussionmentioning
confidence: 95%
“…Considering the fundamental role of physical exercise in healthy aging, a multicomponent training program (MTP) emerges as a possibility of exercise intervention that consists of combining various types of training such as strength training, aerobic training, balance, coordination, and flexibility training [14]. In this context, several studies have already shown the benefits of an MTP on hemodynamic parameters [15,16] and functional capacity [17], as well as improvements in the lipid profile of older women [18,19]. Therefore, this type of training is recommended as a strategy to improve cardiovascular health [20] and physical functioning [21,22], and is advised for older adults in the long term [23,24].…”
Section: Introductionmentioning
confidence: 99%